2016
DOI: 10.1111/jop.12478
|View full text |Cite
|
Sign up to set email alerts
|

Combined CD44, c‐MET, and EGFR expression in p16‐positive and p16‐negative head and neck squamous cell carcinomas

Abstract: High CD44 expression is associated with high c-MET expression, p16-negative tumors, and EGFR-positive tumors. The combination of these markers predicts for poor prognosis in HNSCC patients treated with chemoradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 25 publications
4
32
0
Order By: Relevance
“…In accordance with previously published studies, combined analysis of expression profiles showed that high expression of both, CD44 and EGFR, is significantly associated with p16 negativity. Moreover, significant association between CD44+ and EGFR+ was confirmed by independent test, supporting suggested interactions between CD44 and EGFR.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In accordance with previously published studies, combined analysis of expression profiles showed that high expression of both, CD44 and EGFR, is significantly associated with p16 negativity. Moreover, significant association between CD44+ and EGFR+ was confirmed by independent test, supporting suggested interactions between CD44 and EGFR.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings were supported by recent work of Cohen et al, which introduced so‐called gross staining designation and reported worse OS in patients displaying universal gross staining designation defined by the presence of 90% of tumor showing the same localization of membrane or cytoplasmic CD44 expression. Negative prognostic effect of high expression of CD44 in oral and oropharyngeal cancers in terms of disease‐free survival and/or OS was also presented by Lindquist et al and Nasman et al In our study, patients with CD44+ OPSCC displayed significantly shorter OS and worse LRC on univariate analysis, supporting the results of Baschnagel et al and Motegi et al who reported high CD44 expression as a predictor for worse LRC, PFS and OS, and PFS and LRC rates significantly longer in CD44− patients, respectively.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…After title and abstract checking, 36 studies remained for the further evaluating in details, in which 15 articles were excluded for there were no enough data to calculate the survival rate [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27], one article was removed because of duplication [28]. So, a total of 20 publications were fulfilled the eligibility criteria [5][6][7][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45].…”
Section: Literature Searching and Study Characteristicsmentioning
confidence: 99%
“…Earlier studies have previously described the relation of these markers with survival. EGFR high expression has been associated with a decreased survival rate of OSCC . In particular, EGFR cell sublocalisation could be an important aspect and related to decreased survival.…”
Section: Discussionmentioning
confidence: 99%